Bear the life and times of Augustus Owsley Stanley III - Greenfield, Robert (Thomas Dunne Books, St. Martin's Press, 2016)
Award winning author and biographer Robert Greenfield brings readers the definitive biography of a Grateful Dead legend Augustus Owsley Stanley III, known better by his nickname, Bear. From extensive interviews with Bear and a major Rolling Stone piece, Greenfield brings readers unparalleled access to one of the most important forces in the rise of the counter-culture of the sixties
Includes bibliographical references (pages 253-257), discography (pages 221-232) , and index
Keywords: Stanley, Owsley -- 1935-2011; Grateful Dead (Musical group); Geschichte; Sound engineers -- United States -- Biography; Chemists -- United States -- Biography; LSD (Drug) -- United States -- History -- 20th century; Chemiker; Gegenkultur; LSD; USA; Biografie